Solid state reduction of chromium (VI) pollution for Al2O3–Cr metal ceramics application. (April 2016) - Zhu, Hekai; Fang, Minghao; Huang, Zhaohui; Liu, Yangai; Tang, Hao; Min, Xin; Wu, Xiaowen
Abstract: Reduction of chromium (VI) from Na2 CrO4 through aluminothermic reaction and fabrication of metal-ceramic materials from the reduction products have been investigated in this study. Na2 CrO4 could be successfully reduced into micrometer-sized Cr particles in a flowing Ar atmosphere in presence of Al powder. The conversion ratio of Na2 CrO4 to metallic Cr attained 96.16% efficiency. Al2 O3 –Cr metal-ceramic with different Cr content (5 wt%, 10 wt%, 15 wt%, 20 wt%) were further prepared from the reduction product Al2 O3 –Cr composite powder, and aluminum oxide nanopowder via pressure-less sintering. The phase composition, microstructure and mechanical properties of metal-ceramic composites were characterized to ensure the potential of the Al2 O3 –Cr composite powder to form ceramic materials. The highest relative density and bending strength can reach 93.4% and 205 MP, respectively. The results indicated that aluminothermic reduction of chromium (VI) for metal-ceramics application is a potential approach to remove chromium (VI) pollutant from the environment. Highlights: Chromium (VI) is reduced to Cr particles by aluminothermic reaction. The conversion ratio of Na2 CrO4 to metallic Cr attained 96.16%. The Al2 O3 –Cr composites are used for metal-ceramics application. This work is a potential approach to remove chromium (VI) pollutant.